Staphylococcus aureus capsular material promotes osteoclast formation. - Lau, Y; Wang, W; Sabokbar, A; Simpson, H; Nair, S; Henderson, B; Berendt, A; Athanasou, N (2006)
Osteomyelitis, which is most frequently due to infection by Staphylococcus aureus, commonly causes bone destruction. S. aureus is known to secrete a number of surface-associated proteins that are potent stimulators of bone resorption. The precise cellular and humoral mechanisms that mediate this stimulatory effect are uncertain. In this study, we have determined whether osteoclast formation and resorption is directly promoted by surface-associated proteins. Surface-associated material (SAM) obtained from a 24-hour culture of S. aureus was added to cultures of mouse and human monocytes. Human monocyte cultures were incubated in the presence and absence of a soluble receptor activator of nuclear factor kappa B ligand (RANKL) and macrophage colony stimulating factor (M-CSF). In cultures where M-CSF, RANKL, and SAM were added together, osteoclast formation did not exceed that seen in cultures with M-CSF and RANKL. In keeping with this finding, SAM did not increase osteoclast formation and resorption when mouse monocytes were cocultured with RANKL-expressing osteoblasts. In the absence of RANKL, however, SAM was capable of inducing osteoclast formation in cultures of human monocytes. This finding was evidenced by the generation of vitronectin receptor and tartrate-resistant acid phosphatasepositive multinucleated cells that were capable of lacunar resorption. Inhibitors of RANKL-dependent (RANK:Fc, OPG) and RANKL-independent (anti-TNF-alpha, gp130, IL-8, TGF-beta) osteoclast formation did not inhibit SAM-induced osteoclast formation. SAM did not stimulate mature osteoclast resorption activity. These findings indicate that RANKL, which is present in the circulation as a soluble factor, does not play a role in osteoclast formation in the presence of S. aureus SAM and that S. aureus SAM contains a soluble factor that promotes osteoclast formation by a RANKL-independent mechanism.